COMPARATIVE STUDY BETWEEN ROTA VIRUSES ISOLATED FROM DIARRHEATIC INFANT BABIES AND NEWLY BORN CALVES - Al-Falahy, Raja. H.; Al-Bana, Anton S.; Odisho, Shoney M. (The Iraqi Journal of Veterinary Medicine, 2021)
Rota viruses were isolated in vero continuous cell line from infant babies and newly borne calves affected by diarrhea after treatment in every passage with 10 mg/ml of trypsin and adding 0.5 mg/ml of trypsin in the maintenance media. The isolated viruses induced distinctive and progressive type of cytopatheic effect in infected cells and highest titer was 2x10 6. TCID,50/0.1 for bovine viral isolate. The isolated 50/0.1 for human viral isolate and 2x10 » viruses were identified by indirect fluorescent antibody technique by using reference calf rotavirus antisera. Comparative study were conducted on both human and bovine viral isolate including growth in different cell culture, vero cell line was very sensitive to support growth of both viruses than secondary embryonic calf kidney cell culture, lamb testes and primary embryonic chicken fibroblast cell culture. Both viruses induced morphologically similar kind or plaques in vero cell line but plaqes formed by human isolate were larger in size about 1.5 - 2.5 mm in diameter than those of bovine isolate 1.5 - 2 mm. Cross reactive viral antigens were detected between the isolated viruses in indirect fluorescent antibody technique but not in serum neutralization test by using reference bovine rotavirus antisera.